2017
DOI: 10.21833/ijaas.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Understanding who cyberloafs from the self-control perspective: A study in the public service sector

Abstract: The aim of this study is to understand cyberloafing behavior of employees from the self-control perspective, and to examine differences in cyberloafing according to gender and age, and the gender-age interaction effect. We used survey questionnaires to collect data from 260 Malaysian employees in the public service sector. Our results indicate that the employees engage in cyberloafing with males cyberloafing more than females, irrespective of age. This study contributes to cyberloafing behavior literature by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Meanwhile, this kind of employee's behaviour can contribute the deviance of work and production activities as well as towards the security threats . Cyberloafing can give negative impacts to the organizations and play a factor of deviant behavior (Ahmad & Omar, 2017;Jandaghi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, this kind of employee's behaviour can contribute the deviance of work and production activities as well as towards the security threats . Cyberloafing can give negative impacts to the organizations and play a factor of deviant behavior (Ahmad & Omar, 2017;Jandaghi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It is seen that gender is one of the most associated concepts in the studies on FoMO and cyberloafing (Abel et al, 2016;Arslan et al, 2019;Blanchard & Henle, 2008;Garret & Danzinger, 2008;Przybylsky et al, 2013). Ahmad and Omar (2017) found a significant difference between cyberloafing and gender. In the study, it was found that male employees did more cyberloafing activities compared to female employees.…”
Section: Introductionmentioning
confidence: 90%
“…Individual factors (e.g. age, gender and educational level) were found to be significantly related to CB (Ahmad & Omar, 2017; Baturay & Toker, 2015; Betts et al, 2014; Vitak et al, 2011). For instance, younger employees tend to have higher CB due to exposing to technology and engaging more in online activities compared with older employees (Betts et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, younger employees tend to have higher CB due to exposing to technology and engaging more in online activities compared with older employees (Betts et al, 2014). It was also reported that male public sector service employees engage further with cyberloafing than female employees (Ahmad & Omar, 2017).…”
Section: Introductionmentioning
confidence: 99%